Electrocardiographic changes in 1000 highly trained junior elite athletes. Issue 5 (1st October 1999) - Sharma, S; Whyte, G; Elliott, P; Padula, M; Kaushal, R; Mahon, N; McKenna, W J
Abstract : OBJECTIVES: To evaluate the spectrum of electrocardiographic (ECG) changes in 1000 junior (18 or under) elite athletes. METHODS: A total of 1000 (73% male) junior elite athletes (mean (SD) age 15.7 (1.4) years (range 14-18); mean (SD) body surface area 1.73 (0.17) m2 (range 1.09-2.25)) and 300 non-athletic controls matched for gender, age, and body surface area had a 12 lead ECG examination. RESULTS: Athletes had a significantly higher prevalence of sinus bradycardia (80% v 19%; p<0.0001) and sinus arrhythmia (52% v 9%; p<0.0001) than non-athletes. The PR interval, QRS, and QT duration were more prolonged in athletes than non-athletes (153 (20) v 140 (18) milliseconds (p<0.0001), 92 (12) v 89 (7) milliseconds (p<0.0001), and 391 (27) v 379 (29) milliseconds (p = 0.002) respectively). The Sokolow voltage criterion for left ventricular hypertrophy (LVH) and the Romhilt-Estes points score for LVH was more common in athletes (45% v 23% (p<0.0001) and 10% v 0% (p<0.0001) respectively), as were criteria for left and right atrial enlargement (14% v 1.2% and 16% v 2% respectively). None of the athletes with voltage criteria for LVH had left axis deviation, ST segment depression, deep T wave inversion, or pathological Q waves. ST segment elevation was more common in athletes than non-athletes (43% v 24%; p<0.0001). Minor T wave inversion (less than -0.2 mV) in V2 and V3 was present in 4% of athletes and non-athletes. Minor T wave inversion elsewhere was absent in non-athletes and present in 0.4% of athletes. CONCLUSIONS: ECG changes in junior elite athletes are not dissimilar to those in senior athletes. Isolated Sokolow voltage criterion for LVH is common; however, associated abnormalities that indicate pathological hypertrophy are absent. Minor T wave inversions in leads other than V2 and V3 may be present in athletes and non-athletes less than 16 but should be an indication for further investigation in older athletes.